1-(Pyrrolidin-1-yl)naphtho[1,2-d]isoxazole - Ioannis E. Gerontitis; Abdul kadar Shaikh; Dimitrios Alivertis; Panteleimon G. Takis; Anastassios N. Troganis; Petros G. Tsoungas; George Varvounis (Molbank)
In this study, we examined the oxidation of (E)-2-hydroxy-1-naphthaldehyde oxime with lead tetraacetate in tetrahydrofuran that produced novel (E)-7a,8,9,10-tetrahydro-12H-naphtho[1,2-e]pyrrolo[2,1-b][1,3]oxazin-12-one oxime and 1-(pyrrolidin-1-yl)naphtho[1,2-d]isoxazole and known 7a,8,9,10-tetrahydro-12H-naphtho[1,2-e]pyrrolo-[2,1-b][1,3]oxazin-12-one in 15, 18, and 10% yields, respectively. The oxime is partially hydrolyzed to its corresponding ketone. Modifying the oxidants and reaction conditions did not improve the product yields. Based on previous studies in our laboratory, we proposed that the reactions proceed via the formation of an o-naphthoquinone nitrosomethide intermediate; 1D and 2D NMR, HRMS, IR, and UV-VIS spectra provided information that supported the structure of the products.